SCIENTIFIC AND THEORETICAL FOUNDATIONS OF IMPROVING POPULATION WELFARE THROUGH INFRASTRUCTURE DEVELOPMENT - Abdullaeva, Yulduz Shavkat qizi (THE INNOVATION ECONOMY, 2026)
This article analyzes the scientific and theoretical foundations and practical directions of improving population welfare through infrastructure development. The study evaluates the impact of transport, energy, коммунal, social, and digital infrastructure on living standards, income levels, and employment. Based on statistical analysis and comparative approaches, the socio-economic efficiency of infrastructure development is assessed, and scientific conclusions as well as practical recommendations aimed at improving population welfare are formulated.